As políticas de igualdade racial nos Estados Unidos e no Brasil: constituição, diferenças e similaridades - Jose Carlos Batista (2016)
The object of this research are the public policies of racial equality implemented in the United States between 1960 and 1970, and in Brazil, between 1988 and 2014. The main objective is to analyze, first, the emergence of these policies that point to an inflection in the trajectory oftreatment of racial issues in these two countries that experienced the slavery and abolition in corresponding and similar periods; and, second, to produce an interpretation for both the different time of origin of these policies as well as the differences in the nature, in content, in the formation process of these policies. It starded from two hypotheses: 1º) the emergence of racial equality policies in the United States and Brazil is related to changes in the internal political contexts from the New Deal in the United States and the democratization process in Brazil and external the international political agenda which opened favorable political opportunities to new racial equality ideas and the emergence of political actors to transform these ideas into racial equality policies. 2ª) The differences between the policies are interpreted from the central argument that the institutional legacy of previously established policies in both countries affect the policy reformulation process, which are so dependent on their own trajectory. It carried out an investigation of the historical and political trajectory of the racial issue in both countries emphasizing the key decisions and its development over time. Two main conclusions: 1º) in both countries, in fact, the emergence of these policies is explained by broader contextual changes and the emergence of political actors black movements, political parties and governments which transformed the new racial ideas into racial equality policies. 2ª) The differences between the policies of the two countries at leastthe pioneers, because the later there is a convergence between the two policies are explained by the legacy of previous policies: while the United States was implemented human rights policies for blacks, in a highly confrontational process, in Brazil focused on valorization policies of the history, culture and black identity, in an less confrontational context.